Influence of endodontic irrigants on bond strength between glass-fibre posts and dentin: A systematic review of in vitro studies. (October 2020) - Baldion, Paula Alejandra; Betancourt, Diego Enrique; Gutierrez, Diana Marcela; Beltran, Edgar Orlando; Lafaurie, Gloria Ines; Chambrone, Leandro
Abstract: Irrigant solutions used during and after endodontic treatment on the dentinal surface can influence the bond strength of glass-fibre posts. The aim of this systematic review was to provide an overview of available scientific evidence on the influence of endodontic irrigants on glass-fibre post bond strength. This review followed the Preferred Reporting Items of Systematic Reviews and Meta-Analyses (PRISMA) guidelines. To identify relevant papers, an electronic search was conducted in PubMed, Cochrane, Elsevier, Scopus and EBSCO databases. There were no language restrictions and the last search was conducted to include studies published up to and including July 1, 2019. We searched for in vitro or ex vivo studies that included human or bovine specimens and reported on dentin-fibre post bond strength with the use of different irrigants for root canals. Common variables were identified to consolidate the data, such as bond strength values, interface failure mode and microstructural changes in the dentin after treatments. From 79 potentially relevant papers identified from the database searches, 19 were included in our study for full-text analysis. Authors of this review independently screened search results, extracted data and assessed the risk of bias. Data heterogeneity was present, with differences in dentin type, bond strength tests and irrigation and luting protocols. Current findings suggest that dentin bonding is adversely affected by 5.25% sodium hypochlorite (NaOCl). Chelators adversely affect bonding to root dentin. Antioxidant agents could recover the bond strength between the glass-fibre post and the dentin. Conditioning with phosphoric acid (H3 PO4 ) and NaOCl/ethylenediaminetetraacetic acid (EDTA) with ultrasonic agitation might be recommended in order to remove the smear layer and produce an adequate resin-tag formation. Ageing affects resin cement-dentin bond strength by degradation of collagen fibrils resulting from the activation of endogenous proteases. Therefore, ethanol (EtOH), chlorhexidine (CHX), or cross-linkers can be used to inhibit the activity of matrix metalloproteinases (MMPs) and maintain bond strength over time to achieve greater and longer-term stability of the bonding interface. There are difficulties in achieving an effective resin-root dentin bond. Therefore, this review is clinically significant because recognising the effects of root canal irrigating substances on the retention of glass-fibre posts is essential to improve the prognosis of endodontically treated tooth restorations.